Influence of Deposition Conditions on Structure and Aging of C:H:O Plasma Polymer Films Prepared from Acetone/CO2 Mixtures. Issue 5 (6th April 2014) - Drabik, Martin; Kousal, Jaroslav; Celma, Coralie; Rupper, Patrick; Biederman, Hynek; Hegemann, Dirk
<x xml:space="preserve">Abstract</x> The deposition process of C:H:O plasma polymer films was studied at different experimental conditions such as RF power input and acetone/CO2 gas ratio. Aging of the C:H:O films was studied after their storage both in ambient air and in distilled water at different time scales in order to test their stability. Permanent hydrophilic plasma polymers are obtained showing only minor changes during aging that are mainly connected to oxidation and water (water vapor) adsorption (hydration). The amounts of trapped radicals and oxygen atoms in the films, especially the oxygen bonded in ester groups (OCROR), are of the highest importance in aging. It was found out that the most stable C:H:O plasma polymer films are those for which the elemental ratio O/C is lower than 0.2. These films contain less than 10% of ester groups. With a stable water contact angle of around 55° the C:H:O plasma polymer films appear to be suitable for applications in aqueous environments such as, e.g., in the biomedical field.<inline-graphic xlink:href="ark:/27927/pgg5nqc4m86" content-type="ppap201400005-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />